Healthcare professionals and Basic Knowledge of Medications in Saudi Arabia - Alomi, Yousef Ahmed; Alaskari, Dima Ahmad; Almelf, Malak Mohammad; Badawi, Dima Ali; Alshihri, Abdullah Mohammad (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the Healthcare professionals and Basic Knowledge of Medications in Saudi Arabia. Methods: It is a 4-months cross-sectional survey of healthcare professionals and knowledge of medicines. The survey consisted of two-part, demographic information and second part forty-nine questions divided into four domains. It included domain one: Primary or essential information about healthcare providers medication, domain two: healthcare professionals information about the drug-related problem, domain three: healthcare professionals information about drug-related cost and domain four: Healthcare providers perception of medications. All type of healthcare professionals included in the study. Medline Plus health information and DailyMed-INH elements information from National Institute of Health United State of America were used. The survey was distributed through social media by using what’s App to more than one thousand healthcare professionals overall Kingdom of Saudi Arabia. The survey was made in an electronic format and it analyzed domain one Primary or necessary information about healthcare professionals medication through survey monkey system. Results: The total responders were (188) Healthcare professionals. Of those 177 (95.16%) were Saudi and 9 (4.84%) were non-Saudi. The gender distribution 120 (63.83%) were females and 68 (36.17%) were males. The most of Healthcare professionals were pharmacists 93 (71.54%), followed by nurses 18 (13.85%) and physicians 15 (11.54%). The most type of medications used was anti-hypertension medicines, anti-diabetic medicines, Skin medications and drugs for Respiratory Diseases. The healthcare professionals showed adequate knowledge both complete and incomplete information of the generic name of Medicines 117 (67.6%), the trade name 126 (73.7%), drug strength 128 (73.9%) and dosage form of medication 132 (76.7%). The responders showed adequate knowledge about medications with both complete information and incomplete information about drug indication 159 (85.5%), how to use medications 161 (87 %). The administration time 161 (86.55%), what to do if patient forgot one dose 133 (71.9%), the potential to adhere medication 159 (86.4%) and the time to stop drugs 148 (79.57%). The majority of responders used drug bulletin 126 (69.61%), Health practitioners 123 (67.96%), Internet 108 (59.67%) and Drug Information Center at the hospital 36 (19.89%) as sources of drug information. Conclusion: More than one-third of Healthcare professionals missed complete essential drug information knowledge. Targeting of health care professionals; with individual basic drug information courses for the healthcare professionals through drug information services is required in Saudi Arabia.
Keywords: Healthcare professional; Knowledge; Ministry of Health; Saudi Arabia; Medications